Gala peace atlas - "Barnaby, Frank (ed.)" (London, 1988)
This atlas maps and analyses the roots of peace and war. It confronts the human, nuclear and environmental crises threatening our species and our planet, and it offers constructive proposals not only for our immediate survival, but for long term sustainable peace.
Keywords: Peace